Between Feminism and Islam : Human Rights and Sharia Law in Morocco - Salime, Zakia (Book collections on Project MUSE., 2011)
There are two major women's movements in Morocco: the Islamists who hold shari'a as the platform for building a culture of women's rights, and the feminists who use the United Nations' framework to amend shari'a law. Between Feminism and Islam shows how the interactions of these movements over the past two decades have transformed the debates, the organization, and the strategies of each other. In Between Feminism and Islam, Zakia Salime looks at three key movement moments: the 1992 feminist One Million Signature Campaign, the 2000 Islamist mass rally opposing the reform of family law, and the.